Readiness of public reading libraries to establish a collaborative network in the field of cross-lending A field study in the main library of Mohamed Essami and its annexes – Biskra - bahi, fateheddin; chabounia, omer (Journal of Social Sciences and Humanities, 2024)
This study aims to assess the readiness of the public reading libraries of Biskra to establish a cooperative network in the field of library services in general and the interlending service in particular. The population concerned by the field study consists of 26 librarian, and we relied on the descriptive approach with the questionnaire as information collection tool and the SPSS program for data analysis ,The study concluded that the concerned libraries are currently in the process of being ready to adopt a cooperative network project linking the main library, Mohamed Essami of Biskra and its annexes, to run all library services, especially the interlending service unified, and there are some shortcomings that caused the delay in launching this project, including the lack of follow-up in the libraries under study by administrative guardianship, and the lack of financial support directed to them.